Ekonomi Politik Energi Terbarukan: Peluang dan Tantangan di Indonesia - Mudhoffar, Khosyi; Magriasti, Lince (Multiverse: Open Multidisciplinary Journal, 2024)
This study explores the political economy of renewable energy in Indonesia, focusing on the opportunities and challenges inherent in transitioning to sustainable energy sources. The research addresses critical questions regarding the effectiveness of current policies, the role of political and economic stakeholders, and the barriers to large-scale implementation of renewable energy projects. Employing a mixed-methods approach, this study combines quantitative data analysis of policy impacts and energy outputs with qualitative interviews of key stakeholders, including policymakers, industry leaders, and environmental advocates. The findings indicate that while Indonesia possesses significant potential for renewable energy, substantial obstacles remain, including regulatory inconsistencies, insufficient infrastructure, and economic dependencies on fossil fuels. The study concludes that for Indonesia to fully realize its renewable energy potential, a cohesive policy framework that integrates economic incentives and political support is essential. This research provides actionable insights into how Indonesia can overcome these barriers and outlines strategic recommendations for fostering a more sustainable and resilient energy sector.